Clinical Application of Cone-Beam Computed Tomography of the Rabbit Head: Part 1 – Normal Dentition - Riggs, G. G.; Arzi, Boaz; Cissell, Derek D.; Hatcher, David C.; Kass, Philip H.; Zhen, Amy; Verstraete, Frank J. M. (Frontiers in Veterinary Science, 2016)
Domestic rabbits (Oryctolagus cuniculus) are increasingly popular as household pets; therefore, veterinarians need to be familiar with the most common diseases afflicting rabbits including dental diseases. Diagnostic approaches for dental disease include gross oral examination, endoscopic oral examination, skull radiography, and computed tomography (CT). CT overcomes many limitations of standard radiography by permitting cross-sectional images of the rabbit head in multiple planes without superimposition of anatomic structures. Cone-beam CT (CBCT) is an oral and maxillofacial imaging modality that produces high-resolution images. The objective of this study was to describe and compare the normal anatomic features of the dentition and surrounding maxillofacial structures in healthy rabbits on CBCT and conventional CT. Ten New Zealand white rabbit cadaver heads were scanned using CBCT and conventional CT. Images were evaluated using Anatomage Invivo 5 software. The maxillofacial anatomy was labeled on CBCT images and the mean lengths and widths of the teeth were determined. The visibility of relevant dental and anatomic features (pulp cavity, germinal center, tooth outline, periodontal ligament) were scored and compared between conventional CT and CBCT. The thinnest teeth were the maxillary second incisor teeth at 1.29 ± 0.26 mm and the maxillary third molar teeth at 1.04 ±0.10 mm. In general, it was found that CBCT was superior to conventional CT when imaging the dentition. Importantly, the periodontal ligament was significantly (P<0.01) more visible on CBCT than on conventional CT. Ability to see the periodontal ligament with such detail may allow earlier detection and treatment of periodontal disease in rabbits. This study is the first of its kind and shows the feasibility and yield of CBCT when evaluating the maxillofacial features and dentition in rabbits.